Optical illusion and its kinetic effectiveness as a design trend in the industrial product (Journal of the College of Basic Education, 2022)
The study, tagged (visual illusion and its kinetic effectiveness as a design trend in the industrial product), dealt with the topic of visual illusion and its kinetic effectiveness in the industrial product through achieving kinetic illusion and in terms of pairing the principles of visual illusion and its theories or what is called visual art, which explains how to exploit natural phenomena by The creative artist and transforming it into a visual art by investing the data of visual sensations, as it is an engineering art that is unique from the engineering formations to exploit the visual effects of contrasts, color contrasts, glow of colors, their overlapping, shrinking, extension and spread ... etc., which gives meanings to industrial products and that this research has an importance.